“They would probably just tell me to stop”: anticipated healthcare professionals’ attitudes and barriers to help-seeking in skin picking disorder - Marta Isibor (Journal of Public Mental Health, 2026)
Purpose Skin picking disorder (SPD) is associated with significant distress, however help-seeking remains low. While shame and stigma have been widely documented, less is known about how anticipated healthcare professionals’ attitudes shape decisions to seek support. This study aims to explore how people living with SPD perceive healthcare professionals and how these perceptions influence well-being and engagement with care. Design/methodology/approach A qualitative design using interpretative phenomenological analysis (IPA) was employed. Semi-structured interviews were conducted with seven adults reporting longstanding skin picking. This study represents a secondary, focused analysis of interview material relating specifically to perceptions of healthcare professionals, anticipated stigma and help-seeking. Data were analysed following established IPA procedures. Findings Participants’ narratives indicated that healthcare professionals operate as symbolic gatekeepers of legitimacy. Anticipated trivialisation, moral judgement linked to the self-inflicted nature of the behaviour, and uncertainty about diagnostic legitimacy contributed to reluctance to seek help. Participants frequently questioned whether their difficulties were serious enough to warrant care and expressed ambivalence towards diagnosis and treatment. Expectations of dismissal and misrecognition shaped both self-appraisal and service engagement, even in the absence of direct contact with services. Originality/value This study extends existing qualitative research on SPD by focusing specifically on anticipated healthcare professional attitudes and their influence on help-seeking. By highlighting how perceptions of services function as barriers to care, the findings contribute to understanding stigma and access to support from a public mental health perspective.